Kinetic and thermodynamic investigations of CO2 gasification of coal chars prepared via conventional and microwave pyrolysis - Jiang, Peng; Meng, Yang; Lu, Ziyao; Xu, Lan; Yang, Gang; Luo, Xiang; Shi, Kaiqi; Wu, Tao (2020)
This study examined an isothermal CO2 gasification of four chars prepared via two different methods, i.e., conventional and microwave-assisted pyrolysis, by the approach of thermogravimetric analysis. Physical, chemical, and structural behaviours of chars were examined using ultimate analysis, X-ray diffraction, and scanning electronic microscopy. Kinetic parameters were calculated by applying the shrinking unreacted core (SCM) and random pore (RPM) models. Moreover, char-CO2 gasification was further simulated by using Aspen Plus to investigate thermodynamic performances in terms of syngas composition and cold gas efficiency (CGE). The microwave-induced char has the largest C/H mass ratio and most ordered carbon structure, but the smallest gasification reactivity. Kinetic analysis indicates that the RPM is better for describing both gasification conversion and reaction rates of the studied chars, and the activation energies and pre-exponential factors varied in the range of 78.45–194.72 kJ/mol and 3.15–102,231.99 s−1, respectively. In addition, a compensation effect was noted during gasification. Finally, the microwave-derived char exhibits better thermodynamic performances than the conventional chars, with the highest CGE and CO molar concentration of 1.30% and 86.18%, respectively. Increasing the pyrolysis temperature, gasification temperature, and CO2-to-carbon molar ratio improved the CGE.